OP92 Are social inequalities in early childhood smoking explained by parental smoking patterns? Findings from the UK Millennium Cohort Study. (13th September 2016) - Taylor-Robinson, D; Wickham, S; Campbell, M; Pearce, A
Abstract : Background: Early smoking initiation is socially patterned and is an important determinant of an individual's probability of long-term tobacco dependency, ever stopping smoking and risk of adverse adult health. The aim of this study was to assess the socio-economic gradient in very early smoking (in children in their final year of primary school, five-six years after the UK smoking bans were introduced) and the extent to which any inequality was attenuated after accounting for longitudinal parental smoking patterns. Methods: Analysis of the United Kingdom Millennium Cohort Study, based on 10, 625 children who participated in sweeps of the study at ages 9 months to 11 years. The outcome was early smoking (whether the child had "ever tried a cigarette, even if it was only a single puff?" by age 11). Risk ratios (RRs) and 95% confidence intervals (CI) for early smoking were estimated using poisson regression, according to maternal education, whilst adjusting for baseline confounding. A measure capturing longitudinal exposure to a regular smoker was then entered into the model, as a potential mediator of the association between maternal education and early smoking. Analyses were conducted using Stata/SE with svy commands to account for the sampling design and attrition. Results: Overall 3.1% (95% CI: 2.7–3.6; CI: = 324) children had tried a cigarette by age eleven. The risk of early smoking increased as maternal education decreased; children of mothers with no qualifications were more than six times as likely to have tried a cigarette than children of mothers with degree level qualifications or higher (RR 6.1 [95% CI: 3.6–10.2]). There was a dose-response relationship between number of study waves at which parents reported anyone regularly smoking in front of their child, with the risk of early smoking reaching 6.2 (3.9–9.6) in children whose parents reported anyone regularly smoking in front of their child at all five waves. Controlling for children seeing anyone regularly smoking reduced the RR of early smoking in children of mothers with no qualifications by around half (3.2, 95% CI: 1.9 to 5.5). Conclusion: A limitation of the study is that the smoking variables were based upon self-report. Three percent of children, who had yet to start secondary school, reported trying a cigarette. The risk was much greater in disadvantaged children. Policies to reduce smoking in front of children may reduce inequalities in early uptake of smoking in children by around half.